Brittle Cornea Syndrome: Case Report with Novel Mutation in the PRDM5 Gene and Review of the Literature - Georgia Avgitidou; Sebastian Siebelmann; Bjoern Bachmann; Juergen Kohlhase; Ludwig M. Heindl; Claus Cursiefen (Case Reports in Ophthalmological Medicine)
A 3-year-old boy presented with acute corneal hydrops on the left eye and spontaneous corneal rupture on the right eye. A diagnosis of brittle cornea syndrome was confirmed by molecular analysis. A novel mutation, the homozygous variant c.17T>G, p.V6G, was found in the gene for PR-domain-containing protein 5 (PRDM5) in exon 1. Brittle cornea syndrome is a rare connective tissue disease with typical ocular, auditory, musculoskeletal, and cutaneous disorders. Almost all patients suffer from declined vision due to corneal scarring, thinning, and rupture. The most common ophthalmologic findings include keratoconus, progressive central corneal thinning, high myopia, irregular astigmatism, retinal detachment, and high risk for spontaneous corneal or scleral rupture. In addition to describing the case with a novel mutation here we review the current literature on brittle cornea syndrome pathogenesis, clinical findings, and therapy.